Pharmacokinetics and intraocular pressure–lowering activity of TAK-639, a novel C-type natriuretic peptide analog, in rabbit, dog, and monkey. (December 2019) - Savinainen, Anneli; Prusakiewicz, Jeffery J.; Oswald, Justine; Spencer, Elizabeth; Lou, Zhen; Cohen, Marita Larsson; Rashidzadeh, Hassan; Josiah, Serene
Abstract: TAK-639 is a topical, 9–amino acid, synthetic, C-type natriuretic peptide analog in development for the treatment of primary open-angle glaucoma and ocular hypertension. This study investigated the impact of TAK-639 on intraocular pressure (IOP), the levels of TAK-639 in aqueous humor, and the pharmacokinetic/pharmacodynamic relationship of TAK-639 following topical ocular administration to normotensive female Dutch belted rabbits, beagle dogs, and cynomolgus monkeys. In the IOP studies, rabbits (n = 6/group) and dogs (n = 8/group) received a single topical ocular dose of TAK-639 0.03%, 0.1%, 0.3%, or 0.6% in the right eye and vehicle in the left eye; monkeys (n = 8/group) received TAK-639 0.1%, 0.3%, 0.6%, 0.9%, or 1.2% in the right eye only. IOP was measured pre dose and at various time points from 0.5 to 24 h post dose for rabbits, and 1–48 h post dose for dogs and monkeys. To assess exposure in aqueous humor, another set of animals received a single ocular dose of TAK-639 0.03%, 0.1%, 0.3%, or 0.6% (rabbits, n = 20/group; dogs, n = 14/group) or TAK-639 0.3%, 0.6%, or 1.2% (monkeys, n = 10/group) in both eyes. Aqueous humor and plasma were collected at the same post dose time points at which IOP was measured. Aqueous humor and plasma TAK-639 concentrations were measured by liquid chromatography–mass spectrometry, and pharmacokinetic parameters were estimated with non-compartmental analysis. Topical ocular administration of TAK-639 resulted in a dose-dependent decrease in IOP, with maximum mean decreases in IOP ranging from −8.90% to −34.4% in the rabbit, from −16.5% to −26.4% in the dog, and from −3.43% to −13.5% in the monkey. The duration of the IOP-lowering effect was 12 h in the rabbit and monkey and 48 h in the dog. TAK-639 exposure in aqueous humor (both maximum concentration and area under the curve) was also dose dependent, with maximum concentration ranging from 0.152 to 93.6 ng/mL (0.03% and 0.6% doses, respectively) in rabbits, 0.490–13.8 ng/mL (0.03% and 0.3% doses, respectively) in dogs, and 1.16–18.1 ng/mL (0.3% and 1.2% doses, respectively) in monkeys. The pharmacokinetic/pharmacodynamic profile, when fitted to an inhibitory sigmoidal model, demonstrated that TAK-639 exposure in aqueous humor correlated well with IOP reduction in these species. The TAK-639 exposure in aqueous humor at half maximal IOP reduction (EC50 ) was lower in monkey and dog than in rabbit (0.2 and 0.4 vs. 2.0 ng/mL, respectively). In plasma, quantifiable concentrations of TAK-639 were low and detectable predominantly at early time points. In conclusion, in rabbit, dog, and monkey, a single topical ocular drop of TAK-639 had a significant IOP-lowering effect that correlated well with increases in TAK-639 levels in aqueous humor and resulted in minimal systemic exposure of TAK-639. Highlights: TAK-639 is a topical, cornea-permeable analog of the C-type natriuretic peptide. We assessed intraocular effects of TAK-639 in rabbits, dogs and monkeys. In these species, ocular TAK-639 significantly lowered intraocular pressure. Intraocular pressure lowering correlated well with TAK-639 aqueous humor exposure. Ocular administration of TAK-639 resulted in minimal systemic exposure.